2000
DOI: 10.1080/00927870008826991
|View full text |Cite
|
Sign up to set email alerts
|

Construction of extended affine lie algebras by the twisting process

Abstract: The behavior of objects associated with general extended affine Lie algebras is typically distinct from their counterparts in affine Lie algebras. Our research focuses on studying characters and Cartan automorphisms, which appear in the study of Chevalley involutions and Chevalley bases for extended affine Lie algebras. We show that for almost all extended affine Lie algebras, any finite order Cartan automorphism is diagonal, and its corresponding combinatorial map is a character.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Let K σ c be the subalgebra of K σ consisting of all matrices of the form (3.80) with P = BF −1 . By [4,Lemma 3.17], G σ c = K σ c ⊕ C. It follows that G σ c = G σ ∩ G c if and only if m = 1. Now Lemma 2.56 implies that G σ is tame if m = 1.…”
Section: Also We Havementioning
confidence: 94%
See 2 more Smart Citations
“…Let K σ c be the subalgebra of K σ consisting of all matrices of the form (3.80) with P = BF −1 . By [4,Lemma 3.17], G σ c = K σ c ⊕ C. It follows that G σ c = G σ ∩ G c if and only if m = 1. Now Lemma 2.56 implies that G σ is tame if m = 1.…”
Section: Also We Havementioning
confidence: 94%
“…In [4] it is shown that many examples of EALA (of types D , A 1 , B , C , and BC ) can be obtained as the fixed points of automorphisms of some other EALA (of types A , D , and C ) which may have a simpler structure. Using Theorem 2.65, we are able to give new proofs of the results obtained in [4]. In Examples 3.78 and 3.79 we have provided the details for two cases which seems to be more delicate.…”
Section: Examplesmentioning
confidence: 98%
See 1 more Smart Citation
“…In [Yo2], Yoshii considered ∆−graded Lie algebras whose corresponding finite dimensional split simple Lie subalgebras are of type ∆ red . Yoshii's concept comes from the theory of EALAs, namely, the core of an EALA is a ∆−graded Lie algebra in the sense of Yoshii [Az1,AG]. Yoshii also introduced (∆, G)−graded Lie algebras, ∆ an irreducible finite root system and G an abelian group [Yo2].…”
Section: The Structure Of L Cmentioning
confidence: 99%
“…Namely, up to the choice of a certain derivation and a 2-cocycle, an EALA is determined by its core modulo center, called the centerless core [N1,2]. In [BGKN], [BGK], [AG] and [Yo1], the authors give a complete description of the centerless cores of reduced extended affine Lie algebras (see also [Az1]). …”
Section: Introductionmentioning
confidence: 99%